2015
DOI: 10.3390/molecules20011088
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Herbicidal Activity of Novel 1-(Diethoxy-phosphoryl)-3-(4-one-1H-1,2,3-triazol-1-yl)-propan-2-yl Carboxylic Esters

Abstract: A series of novel compounds, namely 1-(diethoxyphosphoryl)-3-(4-ones-1H-1,2,3-triazol-1-yl)propan-2-yl carboxylic esters, were designed on the basis of the diazafulvene intermediate of imidazole glycerol phosphate dehydratase (IGPD) and high-activity inhibitors of IGPD, and synthesized as inhibitors targeting IGPD in plants. Their structures were confirmed by 1 H-NMR, 13 C-NMR, 31 P-NMR and HR-MS. The herbicidal evaluation performed by a Petri dish culture method showed that most compounds possessed moderate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Thus, 1,2,3‐triazole rings are broadly applicable and can be used in compounds such as antiparasitic, anticarcinogenic, antiviral, bactericidal, antiepileptic, enzyme inhibiting and sleep regulating compounds. The literature also describes other applications for these compounds, for example, in explosives and agrochemicals . The 1,2,3‐triazole 1,4‐disubstituted rings are easy to obtain using “click chemistry” and, as click chemistry was conceived, it has had a great impact in many areas of modern chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 1,2,3‐triazole rings are broadly applicable and can be used in compounds such as antiparasitic, anticarcinogenic, antiviral, bactericidal, antiepileptic, enzyme inhibiting and sleep regulating compounds. The literature also describes other applications for these compounds, for example, in explosives and agrochemicals . The 1,2,3‐triazole 1,4‐disubstituted rings are easy to obtain using “click chemistry” and, as click chemistry was conceived, it has had a great impact in many areas of modern chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…These structures, and other biochemical data, have revealed that, unlike other enzymes, where Mn 2+ can be exchanged with Mg 2+ or Zn 2+ with little effect on activity ( Andreini et al., 2008 ), IGPD has both a structural and mechanistic requirement for manganese ( Petersen et al., 1997 ). Analysis of the IGPD1 structure, coupled with the observation that triazole-phosphonate compounds are potent inhibitors of the enzyme ( Hawkes et al., 1993; Jin et al., 2015; Lindell et al., 1996; Mori et al., 1995 ), has suggested that the reaction ( Figure 1 A) proceeds via an initial high-energy deprotonation of the substrate imidazole ring (p K a ∼14.5) to yield an anionic imidazolate ( Walba and Isensee, 1961 ), which is then converted to the product via diazafulvene and enol intermediates. Since the substrate lacks a carbonyl or imine adjacent to the leaving proton, which is thus non-acidic, IGPD uses an unusual mechanism for catalysis that is distinct from other dehydration reactions that have been reported to date ( Glynn et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…1117,1128 Nevertheless, modification of this moiety allows for further synthetic exploration of new active site pockets and provides a handle for the modification of physiochemical properties for this class of inhibitor. 1128 It remains unclear if compounds containing an amine or amide group are able to coordinate to the Mn 2+ ion in the same manner as diazafulvene, as structural characterization of theses inhibitors has not been reported. However, it is likely that hydroxyl, amine, amide, and ester groups at this position are able to engage in hydrogen bonding interactions with the proximal A’ Glu21 residue.…”
Section: Lyases (Ec 4x)mentioning
confidence: 99%